Tannins in the Treatment of Diabetic Neuropathic Pain: Research Progress and Future Challenges - Omar, Norsuhana; Ismail, Che Aishah Nazariah; Long, Idris (Frontiers in Pharmacology, 2022)
Diabetes mellitus and its consequences continue to put a significant demand on medical resources across the world. Diabetic neuropathic pain (DNP) is a frequent diabetes mellitus chronic microvascular outcome. Allodynia, hyperalgesia, and aberrant or lack of nerve fiber sensation are all symptoms of DNP. These clinical characteristics will lead to worse quality of life, sleep disruption, depression, and increased mortality. Despite the availability of numerous medications that alleviate the symptoms of DNP, the lack of long-term efficacy and unfavorable side effects highlight the urgent need for novel treatment strategies. This review paper systematically analyzed the preclinical research on the treatment of DNP using plant phytochemicals that contain only tannins. A total of 10 original articles involved in in-vivo and in-vitro experiments addressing the promising benefits of phytochemical tannins on DNP were examined between 2008 to 2021. The presented information suggests that these phytochemicals can be used to treat DNP through their antihyperalgesic, anti-inflammatory, and antioxidant effects.